Brain mechanisms of eye contact during verbal communication predict autistic traits in neurotypical individuals - Jiang, Jing (Sci Rep, 2020)
Atypical eye contact in communication is a common characteristic in autism spectrum disorders. Autistic traits vary along a continuum extending into the neurotypical population. The relation between autistic traits and brain mechanisms underlying spontaneous eye contact during verbal communication remains unexplored. Here, we used simultaneous functional magnetic resonance imaging and eye tracking to investigate this relation in neurotypical people within a naturalistic verbal context. Using multiple regression analyses, we found that brain response in the posterior superior temporal sulcus (pSTS) and its connectivity with the fusiform face area (FFA) during eye contact with a speaker predicted the level of autistic traits measured by Autism-spectrum Quotient (AQ). Further analyses for different AQ subclusters revealed that these two predictors were negatively associated with attention to detail. The relation between FFA–pSTS connectivity and the attention to detail ability was mediated by individuals’ looking preferences for speaker’s eyes. This study identified the role of an individual eye contact pattern in the relation between brain mechanisms underlying natural eye contact during verbal communication and autistic traits in neurotypical people. The findings may help to increase our understanding of the mechanisms of atypical eye contact behavior during natural communication.